Biologic TNF inhibiting agents for treatment of rheumatoid arthritis: Persistence and dosing patterns in Germany - Sarah Neubauer; Mary Cifaldi; Thomas Mittendorf; Arijit Ganguli; Malte Wolff; Jan Zeidler (Health Economics Review, 2014)
Objective: To obtain detailed real-world data on persistence and dosing patterns in the utilisation of the TNF inhibitors adalimumab, etanercept, and infliximab in rheumatoid arthritis (RA) patients treated in Germany. Methods: In this retrospective observational study claims data of a major German health insurance fund between 2005 and 2008 were analysed. Patients receiving at least one prescription of adalimumab, etanercept or infliximab were identified and categorised as "TNF inhibitor naive" or "TNF inhibitor continuing". For the calculation of TNF inhibitor persistence a survival analysis with the Kaplan-Meier estimator was used. A Cox regression was used to analyse, if any relevant factors were influencing persistence. Dosage increase rates were analysed for adalimumab, etanercept and infliximab. Sensitivity analyses based on variations in gap length were conducted. Results: A total of 2,201 RA patients were identified. 1,468 of these patients were TNF inhibitor naive patients and 733 were defined as TNF inhibitor continuing patients. There were no significant differences in the treatment persistence rates between adalimumab, etanercept and infliximab for TNF inhibitor naive and continuing patients. The persistence rate after three years was 22.47% for adalimumab, 24.27% for etanercept and 21.49% for infliximab naive patients. For continuing patients, the persistence rate after three years was 32.88% for adalimumab, 30.95% for etanercept, and 33.90% for infliximab, respectively. Gender, medication and Charlson Comorbidities Index did not influence the persistence significantly. Dosage increase occurred in 7.3% adalimumab, 1.4% etanercept, and 17.2% infliximab naive patients and 5.8%, 1.1% and 11.9% respectively in the continuing patients. Conclusions: In this study, there were no significant differences in persistence among adalimumab, etanercept and infliximab treated patients. Consistent with previous research, there was a higher dose escalation for infliximab than for the two subcutaneous treatments, adalimumab or etanercept.
Keywords: 330; Rheumatoid arthritis; Claims data; Persistence; Dosing patterns; Germany; Tumor necrosis factor inhibitor